The high expression of MTH1 and NUDT5 predict a poor survival and are associated with malignancy of esophageal squamous cell carcinoma - Wang, Jing-Jing (PeerJ, 2020)
BACKGROUND: MTH1 and NUDT5 effectively degrade nucleotides containing 8-oxoguanine. MTH1 and NUDT5 have been linked to the malignancy of multiple cancers. However, their functions in tumor growth and metastasis in esophageal squamous carcinoma (ESCC) remain obscure. Our present study aims to explore their prognostic value in ESCC and investigate their function in MTH1 or NUDT5-knockout tumor cells. METHODS: MTH1 and NUDT5 protein expression in ESCC adjacent normal tissues and tumor tissues was examined by immunohistochemistry staining. Kaplan–Meier curves were used to assess the association between their expression and overall survival (OS) in ESCC patients. Univariate and Multivariate Cox regression analyses were generated to determine the correlation between these protein expression and OS of ESCC patients. Protein expression in ESCC cell lines were measured by Western blotting. To explore the potential effects of the MTH1 and NUDT5 protein in ESCC, cell models with MTH1 or NUDT5 depletion were established. CCK-8, cell cycle, Western blotting, migration and invasion assays were performed. RESULTS: Our present study demonstrated that the levels of MTH1 and NUDT5 were upregulated in ESCC cell lines and ESCC tissues, the expression of MTH1 and NUDT5 in ESCC tissues was significantly higher than in adjacent non-tumorous, and higher levels of MTH1 and NUDT5 predicted a worse prognosis in patients with ESCC. MTH1 and NUDT5 are novel biomarkers of the progression of ESCC and a poor prognosis. We also found for the first time that the high expression of NUDT5 independently predicted lower OS in patients with ESCC (hazard ratio (HR) 1.751; 95% confidence interval (CI) [1.056–2.903]; p = 0.030). In addition, the depletion of MTH1 and NUDT5 strongly suppressed the proliferation of ESCC cells and significantly delayed the G1 phase of the cell cycle. Furthermore, we found that MTH1 and NUDT5 silencing inhibited epithelial–mesenchymal transition mainly by the MAPK/MEK/ERK dependent pathway, which in turn significantly decreased the cell migration and invasion of ESCC cells. Our results suggested that the overexpression of MTH1 and NUDT5 is probably involved in the tumor development and poor prognosis of ESCC.